Impact of adding Mediterranean diet to aerobic and strengthening exercise program on pain, inflammation, and muscle performance in females with rheumatoid arthritis: a randomized controlled trial - Abdel-Aal, Nabil M.; Kamil, Ragia M.; Tayel, Dalia I.; Hamed, Rania H.; Ragab, Mohamed M.; Abd El-Azeim, Alshaymaa S. (Physiotherapy theory and practice, 2025)
People with rheumatoid arthritis (RA) frequently use dietary interventions such as Mediterranean diet (MedDiet) and exercises to complement pharmacotherapy. To investigate the effect of adding MedDiet to a designed exercise program on quadriceps and hamstrings muscles performance, pain, C-reactive protein (CRP), handgrip strength, bodyweight, and function in females with RA. Sixty females were allocated randomly to the MedDiet plus exercise program ( = 30) or exercise program only ( = 30). The interventions continued for 6 months followed by 6 months of follow-up with no intervention. The primary outcome was the quadriceps and hamstrings muscles performance (agonist-antagonist ratio). The secondary outcomes were visual analog scale (VAS) for pain, CRP blood marker for inflammation, handheld dynamometer for handgrip strength, Health AssessmentQuestionnaire disability index (HAQ-DI) for function, and body weight. All outcomes were measured at baseline, 6-month post-intervention, and 12 months from baseline as a follow-up. The MedDiet group showed statistically significant improvements in all the measured outcomes than the control group ( < .05) after 6 and 12 months. After 6 months of intervention, the mean±SD for agonist-antagonist ratio, pain, and HAQ-DI were 84.59 ± 5.33 and 69.92 ± 5.56 ( < .001, ƞ = 0.65), 42.33 ± 8.98 and 54.33 ± 10.06 ( < .001, ƞ = 0.3), 1.13 ± 0.48 and 1.9 ± 0.59 ( < .001, ƞ = 0.34) in the MedDiet and control groups, respectively. Adding MedDiet to aerobic and strengthening exercise program improved quadriceps and hamstrings muscles performance, pain, functional ability, CRP, handgrip strength, and body weight. Consequently, Mediterranean diet should be considered as adjunctive therapy in treating females with RA.